Green Environment in the EU Countries: The Role of Financial Inclusion, Natural Resources and Energy Intensity - Hodzic, Sabina; Sikic, Tanja Fatur; Dogan, Eyup (Elsevier Sci Ltd, 2023)
The European Union pursues the European Green Deal strategy as well as Sustainable Development Goals, the main target of which is to become a carbon-neutral continent by 2050. Hence, a lot of environmental challenges need to be solved. Possible determinants in mitigating environmental challenges are financial inclusion, natural resources and interaction with a green environment. This concept implies preserving natural resources and a clean environment for future generations. However, there is still no clear evidence in the literature on how natural resources and financial inclusion interact with the green environment in the EU. Therefore, this paper aims at filling this gap. In order to obtain empirical results, the quantile regression econometric technique proposed by Koenker has been applied. The analyzed period was from 2004 to 2019 for EU-26 countries. The results show that higher energy intensity is the main cause of environmental degradation. However, financial inclusion in higher quantiles and natural resources rent lead to a reduction in carbon emissions. Our results also confirm that the EU has succeeded in decoupling economic growth from pollution. The robustness of the results was checked using a Powell's quantile regression, which confirmed the relationship between a green environ-ment and the variables analyzed. Thus, the results suggest that financial inclusion needs to be more integrated into energy and climate policies, especially in the early stages of development. In addition, large-scale green investments are needed in EU countries to further reduce energy intensity and create an effective green environment.
Fatur Sikic, Tanja/0000-0003-2456-150X; Hodzic, Sabina/0000-0002-4202-3548; Dogan, Eyup/0000-0003-0476-5177;
Keywords: Financial Inclusion; Natural Resources Rent; Energy Intensity; Green Environment; Quantile Regression Analysis